The advertisement call of Leptobrachella dushanensis (Anura, Megophryidae) - Jing Liu; Yanlin Cheng; Shize Li; Gang Cheng; Gang Wei (Herpetozoa)
We describe the advertisement call of the Dushan Leaf Litter Toad, Leptobrachella dushanensis, based on recordings obtained from three individuals from its type locality. The advertisement call of L. dushanensis consists of a single note with a dominant frequency of 4.84–4.91 kHz. Furthermore, we compare the differences in advertisement calls between L. dushanensis and its sister species, Leptobrachella dong. The advertisement calls of L. dushanensis and L. dong can be clearly distinguished. Our findings provide bioacoustic evidence supporting the taxonomic status of L. dushanensis and provide basic data for future behavioral and ecological studies on Leptobrachella.